1899 N.C. Sess. Laws 250 - (:unkn) unknown (My University, 1899)
Pub. Laws, ch. 120, § 1: That it shall be unlawful for any person wantonly or in sport to shoot or discharge any gun or pistol in or within one hundred yards of any street in any public road leading out of the towns of Sparta in Alleghany county and Jefferson in Ashe county for a distance of one-fourth mile from the court houses in said towns
Keywords: DISCHARGE